Acute Otorrhea in Children with Tympanostomy Tubes. Issue 4 (April 2015) - van Dongen, Thijs M. A.; Venekamp, Roderick P.; Wensing, Annemarie M. J.; Bogaert, Debby; Sanders, Elisabeth A. M.; Schilder, Anne G. M.
<x xml:space="preserve">Abstract</x> Background: Acute tympanostomy-tube otorrhea is a common sequela in children with tympanostomy tubes. Acute tympanostomy-tube otorrhea is generally a symptom of an acute middle ear infection, whereby middle ear fluid drains through the tube. The widespread use of pneumococcal conjugate vaccination (PCV) has changed the bacterial prevalence in the upper respiratory tract of children, but its impact on bacterial and viral pathogens causing acute tympanostomy-tube otorrhea is yet unknown. Methods: This study was performed in the post-PCV7 era parallel to a randomized clinical trial of the clinical and cost–effectiveness of ototopical and systemic antibiotics and initial observation in 230 children aged 1 to 10 years with untreated, uncomplicated acute tympanostomy-tube otorrhea. Otorrhea and nasopharyngeal samples were collected at baseline (before treatment) and at 2 weeks (after treatment). Conventional bacterial culture was performed followed by antimicrobial-resistance assessment. Viruses were identified by polymerase chain reaction. Results: At baseline, Haemophilus influenzae (41%), Staphylococcus aureus (40%) and Pseudomonas aeruginosa (18%) were the most prevalent bacteria in otorrhea, followed by Streptococcus pneumoniae (7%) and Moraxella catarrhalis (4%). Most pneumococci were non-PCV7 serotypes. Viruses were detected in 45 otorrhea samples at baseline (21%). Most infections were polymicrobial and overall antimicrobial resistance was low. Conclusions: H. influenzae, S. aureus and P. aeruginosa are the most common microorganisms in children with untreated uncomplicated acute tympanostomy-tube otorrhea. Prevalence of S. pneumoniae has decreased since the introduction of PCV and most pneumococci are nonvaccine serotypes.